Study of Porous Structures and Thermal Properties of Luminescent Polymeric Microspheres Derivatives of Naphthalene-2,7-Diol - Beata Podkościelna; Mateusz Lutomski (Adsorption Science & Technology)
We studied the porous structures and thermal properties of spherical shaped cross-linked polymers. These novel polymeric microspheres were synthesized by emulsion–suspension polymerization of aromatic tetrafunctional monomer [2,7-(2-hydroxy-3-methacryloyloxypropoxy)naphthalene (2,7-NAF.DM)] with typical, commercially available monomers (styrene, divinylbenze ne and methyl methacrylate). The monomer 2,7-NAF.DM was obtained in the two-step process. In the first step, the epoxy resin was synthesized by treating epichlorohydrin with naphthalene-2,7-diol. In the second step, the obtained epoxy derivatives were subjected to esterification with methacrylic acid. Porous structures of the obtained microspheres in the dry state were studied by nitrogen adsorption–desorption measurements. Thermal stabilities and degradation behaviours of the obtained co-polymers were characterized by differential scanning calorimetry and thermogravimetric/derivative thermogravimetry analyses. In addition, we also present the photoluminescent properties of these microspheres.